Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/01635581.2017.1359314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic and Intermittent Calorie Restriction on Adropin Levels in Breast Cancer

Abstract: Adropin is a peptide hormone that has been implicated in insulin resistance and as a potential regulator of growth. The aim of this study is to determine the effect of calorie restriction on circulating levels of adropin in the MMTV-TGFα breast cancer mouse model and investigate the effects of adropin peptide on the viability of MCF-7 and MDA-231 breast cancer cells in culture. Ten-week-old mice were assigned to either ad libitum-fed (AL), chronic calorie-restricted, or intermittent calorie-restricted groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…The positive correlation between plasma adropin concentration and age in this study differs from previous results from humans and rodents showing a decline with aging (8,48,60,61). There are two potential explanations for the discrepancy that also serve as a precaution when comparing results between studies.…”
Section: Editors' Pick: Adropin Signals Risk For Metabolic Dysregulatcontrasting
confidence: 90%
“…The positive correlation between plasma adropin concentration and age in this study differs from previous results from humans and rodents showing a decline with aging (8,48,60,61). There are two potential explanations for the discrepancy that also serve as a precaution when comparing results between studies.…”
Section: Editors' Pick: Adropin Signals Risk For Metabolic Dysregulatcontrasting
confidence: 90%
“…However, against these data Gao et al (48) tried ADR treatment of diet-induced obesity with IR mice and found ADR treatment enhanced glucose tolerance, ameliorates IR and promotes preferential use of carbohydrate over fat in fuel selection and indicated a negative relationship between ADR level and high blood glucose level and IR; thus supporting the findings of the current study. Thereafter, Tuna et al (15) experimentally detected high serum ADR levels among animals received calorie-restricted diet, while was significantly lower among animals maintained on normal calorie intake, thus supporting the inverse correlation between serum ADR levels and calorie intake.…”
Section: Discussion:-mentioning
confidence: 91%
“…ADR is a 42-aminoacid peptide hormone which is highly conserved across mammalian species through open reading frame in exon 2 that encodes the full-length 75-amino acid peptide; 33-amino acid as secretory signal peptide and the biologically active ADR (13) . ADR is abundant in liver and secreted into the circulation and its plasma concentrations are highly regulated by energy intake (15) and functions to preserve the circulatory system through regulating endothelial function and activity of endothelial nitric oxide (16) .…”
mentioning
confidence: 99%
“…Therefore, GPR19 activation may promote carcinogenesis and metastases formation by promoting mesenchymal-to-epithelial cell transition. On the other hand, is was reported that adropin is able to suppress viability and induce apoptosis in the breast cancer MCF-7 cell line [64]. Thus, the role of adropin and its therapeutic potential in breast cancer is unclear and requires more experiments.…”
Section: Adropin and Cancermentioning
confidence: 99%